THE RELATIONSHIP OF FAMILY ROLES TO MEDICATION ADHERENCE IN SCHIZOPHRENIA PATIENTS - Rindayati, Rindayati; Nasir, Abdul; Rizal, Chusnul (Journal of Vocational Nursing, 2021)
Introduction: Schizophrenia is a chronic mental illness with symptoms of hallucinations, delusions and inappropriate behavior. Patients require long-term treatment, but many do not adhere to treatment. The purpose of the study was to determine whether there was a relationship between family roles and adherence to medication for schizophrenic patients. Methods: The research design used correlation with a cross-sectional approach. The population of this study was 60 families with schizophrenia who visited the mental polyclinic of Ibnu Sina Hospital on 7-13 July 2019. The sampling technique used accidental sampling with a total sample of 52 respondents. Collecting data on family roles based on Friedman's theory and medication adherence using the Morisky Medication Adherence Scale. The research test used the Spearman rank test SPSS. Ethical Approval by Faculty of Nursing Universitas Airlangga number 1601-KEPK, July 17, 2019. Results: The results of this study showed that the role of the good family was 53.8% and the role of the less family was 46.2%. The medium level of adherence to taking medication was 42.3% and less level of adherence to taking medication was 32.7%. The results of the Spearman test are rho count 0.403 > rho table 0.271, which means that there is a significant relationship. Conclusion: The role of the family is related to medication adherence for schizophrenic patients.